Bioequivalence and Pharmacokinetics of Two Formulations of Amlodipine Tablets in Healthy Subjects - Jaafar J. Ibraheem Al-Tamimi (College of Pharmacy University of Baghdad, 2017)
The bioequivalence of a single dose tablet containing 5 mg amlodipine as a test product in comparison to NorvascÂ® 5 mg tablet (Pfizer USA) as the reference product was studied. Both products were administered to twenty eight healthy male adult subjects applying  a fasting, single-dose, two-treatment, two-period, two-sequence, randomized crossover design with two weeks washout period between dosing. Twenty blood samples were withdrawn from each subject over 144 hours period. Amlodipine concentrations were determined in plasma by a validated HPLC-MS/MS method. From the plasma concentration-time data of each individual, the pharmacokinetic parameters; Cmax, Tmax, AUC0-t, AUC0-Â¥, Cmax/AUC0-Â¥, lZ, T0.5, MRT, Cl/F and Vd/F; were calculated applying non-compartmental analysis. The average values of the above parameters  for the test formula were 1.99 ng/ml, 8.3 hours, 82.87 ng.hr/ml, 95.23 ng.hr/ml, 0.0219 hr-1, 0.018 hr-1, 38.5 hr, 56.2 hr, 60.9 l/hr and 3483 liters, respectively. The average values of these parameter for the reference formula were 1.92 ng/ml, 7.9 hours, 76.3 ng.hr/ml, 89.31 ng.hr/ml, 0.0225hr-1, 0.019  hr-1, 36.7 hr, 59.9 hr, 69.5 l/hr, and 3983.4 liters, respectively. The pharmacokinetic parameters mentioned above were statistically analyzed by ANOVA test. Ln-transformed values of the pharmacokinetic parameters used for bioequivalence testing; Cmax, AUC0-t and AUC0-Â¥ ; were also statistically analyzed by ANOVA, 90% Confidence Interval (CI) and Schuirmannâ€™s two one-sided t-tests. For the Tmax, parametric and nonparametric tests were applied. Based on FDA criteria on bioequivalence, the results of the above statistical tests demonstrated bioequivalence of the two products. Keywords: Amlodipine, Pharmacokinetic, Bioequivalence , HPLC/MS/MS.